2019
DOI: 10.1117/1.nph.6.4.045009
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the severity of hypoxic-ischemic brain injury in a neonatal preclinical model using measurements of cytochrome-c-oxidase from a miniature broadband-near-infrared spectroscopy system

Abstract: We describe the development of a miniaturized broadband near-infrared spectroscopy system (bNIRS), which measures changes in cerebral tissue oxyhemoglobin (½HbO 2) and deoxyhemoglobin ([HHb]) plus tissue metabolism via changes in the oxidation state of cytochrome-c-oxidase ([oxCCO]). The system is based on a small light source and a customized mini-spectrometer. We assessed the instrument in a preclinical study in 27 newborn piglets undergoing transient cerebral hypoxia-ischemia (HI). We aimed to quantify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…In a study combining bNIRS and 31 P MRS in 22 piglets we showed that following HI the recovery of oxCCO was correlated with the recovery of nucleotide‐triphosphate (NTP)/total exchangeable phosphate pool (epp) and outcome (Bainbridge et al., 2013). Our results suggested that if NTP/epp and oxCCO recovery is not above a threshold following HI, unfavorable outcome is likely (Kaynezhad et al., 2019). In addition, we observed that the measurements of the changes in brain tissue hemoglobin difference (HbD = HbO 2 − HHb) which is indicative of brain oxygenation show a poor correlation with NTP/epp and outcome.…”
Section: Neonatal Neurological Monitoring: Advances In Diffuse Opticsmentioning
confidence: 67%
See 1 more Smart Citation
“…In a study combining bNIRS and 31 P MRS in 22 piglets we showed that following HI the recovery of oxCCO was correlated with the recovery of nucleotide‐triphosphate (NTP)/total exchangeable phosphate pool (epp) and outcome (Bainbridge et al., 2013). Our results suggested that if NTP/epp and oxCCO recovery is not above a threshold following HI, unfavorable outcome is likely (Kaynezhad et al., 2019). In addition, we observed that the measurements of the changes in brain tissue hemoglobin difference (HbD = HbO 2 − HHb) which is indicative of brain oxygenation show a poor correlation with NTP/epp and outcome.…”
Section: Neonatal Neurological Monitoring: Advances In Diffuse Opticsmentioning
confidence: 67%
“…Regarding bNIRS, the relative changes of oxCCO needs to be assessed with respect to other systemic or cerebral changes; hence allowing a better interpretation of the physiology as recently demonstrated by our group (Mitra et al., 2019; Bale et al., 2018). However, in preclinical studies when the initial hypoxic‐ischemic insult is recorded this measurement has demonstrated a great potential to predict the MRS metabolic markers and assess injury severity (Bainbridge et al., 2013; Kaynezhad et al., 2019). DCS can provide an absolute measurement of blood flow and therefore CMRO 2 , it also suffers from limitations that are intrinsic to all optical monitoring such as motion artifacts and tissue inhomogeneities.…”
Section: Neonatal Neurological Monitoring: Advances In Diffuse Opticsmentioning
confidence: 99%
“…Mitochondrial activity in the retinae of mice were measured in real time using a miniature broadband near-infrared spectroscopy (bNIRS) system called miniCYRIL (Cytochrome Research Instrument and application) described previously 16 , 46 . miniCYRIL consists of a miniature halogen-based white light source (HL2000-HP) and a miniature spectrometer (QE65 pro) by Ocean Optics, USA.…”
Section: Methodsmentioning
confidence: 99%
“…The oxCCO measurement has been used in our previous animals and human studies as a reliable marker for cellular oxidative metabolism 31 , 46 , 49 52 . Changes in total hemoglobin (Δ[HbT] = Δ[HHb] + Δ[HbO 2 ]) as a measure for retinal blood volume as well as hemoglobin difference (Δ[HbDiff] = Δ[HbO 2 ] − Δ[HHb]), which is indicative of retinal oxygenation, were also derived.…”
Section: Methodsmentioning
confidence: 99%
“…Conventional functional near-infrared spectroscopy systems, in contrast, have just 2-3 wavelengths of light and thus can only be used to measure concentration changes in oxygenated hemoglobin (HbO 2 ) and deoxygenated hemoglobin (HHb) in the blood vessels surrounding the brain areas of interest. The intracellular BNIRS measure of oxCCO has been validated both in animal and human studies, for example, demonstrating its correlation with phosphorous magnetic resonance spectroscopy ( 31 P MRS) measures of nucleotide triphosphate levels (which is mainly ATP) (Peeters-Scholte et al, 2004;Bainbridge et al, 2014;Kaynezhad et al, 2019) and measures of the lactate/pyruvate ratio, a marker of aerobic metabolism (i.e., mitochondrial ATP synthesis), as obtained with microdialysis (Tisdall et al, 2008; for review, see Bale et al, 2016).…”
Section: Bnirs Methodologymentioning
confidence: 99%